Diel vertical migration of Cladocera in a compartment of a tropical reservoir - Erika dos Santos Silva; Odete Rocha; Maria José dos Santos-Wisniewski (Acta Limnologica Brasiliensia, 2018)
Abstract Aim This study seeks to analyze the vertical migration pattern of Cladocera species as related with the physical and chemical parameters of the water. Methods Samplings were carried out at 3-h intervals for 24 h in January 15 on the Sapucaí River compartment of Furnas reservoir, Minas Gerais State, Brazil. These samples were taken at five depths, from the surface to the near-bottom layer (0, 2, 4, 6, 8, and 9 m) totalizing 54 samplings for each limnological variable (temperature, pH, dissolved oxygen, electrical conductivity, chlorophyll-a content, Index of Trophic State, water transparency and Cladocera populations abundance). The samplings were performed at the limnetic region at a point with total depth of 9 meters. Results Water column thermal and chemical stratifications and thermocline occurrences were registered in the middle of the day. Among the 14 Cladocera species, only Ceriodaphnia cornuta and C. silvestrii displayed a significant migration pattern, which was mainly related to chlorophyll-a and dissolved oxygen concentrations. Diaphanosoma birgei and D. spinulosum are found at high densities near the surface and low ones in depth. The migration of Diaphanosoma was directly related to the concentration of chlorophyll a and pH, thus acting as a limiting factor. Feeding at high temperatures in the surface layer and assimilating at lower ones in depth, usually confer metabolic advantages to the vertically migratory species. Conclusions In this study, a well-defined pattern of vertical migration was found for two Cladocera species and its possible causes were hypothesized. To the species with less locomotory capacity, thermal and chemical stratifications can act as barriers to migration and distribution through the water column. This pattern may probably be found for zooplankton species in other compartments of Furnas reservoir, with similar physical and chemical properties.